Production of H2-rich syngas and CO2 capture from the steam gasification of human and animal derived bio-solids: Comparison with a valorization study for soil amendment - Vamvuka, Despina; Sfakiotakis, Stelios; Kyriakidis, Konstantinos; Papakyriakopoulos, Ioannis (Edelweiss Applied Science and Technology, 2026)
The steam gasification of human and animal-derived biosolids, integrated with CO2 capture by a waste material, was investigated for the production of a H2-rich syngas fuel. The potential of biochars to be used alternatively for soil amendment was also examined. A fixed-bed reactor/differential thermogravimetric-mass spectrometry system and column leaching were employed for the experiments, respectively. By sorbent addition, 86-87 % of CO2 was captured, elevating the H2 fraction in the generated gas by 80.1-104.5 % and the H2/CO ratio up to 4-6 times. The gasification of animal bio-solid produced not only a higher yield of H2, 3.1 m3/kg, than human bio-solid, but also H2 of higher purity, 84.3 mol%. When the biochars were leached through a quartzitic soil, some retention of nitrates occurred on the biochar’s surface, while the release of phosphorus was negligible. The leachability of alkali cations, Ca, Mg, and K, was higher in the case of the animal biochar/soil system, whereas that of heavy metals was very low or practically null, supported by the neutral to alkaline pH of the leachates. Overall, the steam gasification of the bio-solids studied, in the presence of other wastes used as CO2 sorbents, proved to be very advantageous. On the other hand, the application of biochars with composts or other wastes could improve soil amendment.